Relevansi Antropologi dalam Kajian Kesenian di Indonesia - Gabriel Roosmargo Lono Lastoro Simatupang (Universitas Andalas, 2023)
This article aims to review how anthropology and art pay attention to art, especially to similar studies that have been carried out in Indonesia. Based on this, it is also to show the implicit meaning of some propositions and associations of ideas from an anthropological perspective that can be considered for the study of art. In this sense, it is not to solve the great questions of the anthropology of art or confine oneself to the virtues of anthropology for art but to broaden the horizons in which they must be considered.